2022
DOI: 10.2147/jir.s377804
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and the Role of the Albumin-to-Globulin Ratio in Predicting Recurrence Among Patients with Idiopathic Granulomatous Mastitis

Abstract: Background Idiopathic granulomatous mastitis (IGM) is a rare inflammatory disease of the breast with a high recurrence rate. The serum albumin to globulin ratio (AGR) is a relatively novel biomarker in inflammatory diseases, and one whose role in the recurrence of IGM remains unknown. This study primarily investigated the potential risk factors for IGM recurrence and whether AGR can be used as a predictive factor. Methods Patients diagnosed with IGM from pathology repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
(113 reference statements)
3
5
0
Order By: Relevance
“…The results illustrate that NPM patients with nipple deformity are more likely to receive milder assessment results (p < 0.001), which is consistent with previous studies assuming that the reason for restricted subareolar abscesses in these patients is associated with squamous metaplasia of lactiferous ducts [31] . The current study only observed the effects of age and smoking among NPM patients without NI, both of which agree with NPM clinical features and previous studies although those studies did not stratify the NPM patients by breast duct structure [28,32] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results illustrate that NPM patients with nipple deformity are more likely to receive milder assessment results (p < 0.001), which is consistent with previous studies assuming that the reason for restricted subareolar abscesses in these patients is associated with squamous metaplasia of lactiferous ducts [31] . The current study only observed the effects of age and smoking among NPM patients without NI, both of which agree with NPM clinical features and previous studies although those studies did not stratify the NPM patients by breast duct structure [28,32] .…”
Section: Discussionsupporting
confidence: 91%
“…This study investigates the effect of several covariates such as nipple deformity, age, smoking, external force, and autoimmune, and the conclusion is agreeable to previous studies that the effect of these factors differed from the breast structure [13,[28][29][30] . The results illustrate that NPM patients with nipple deformity are more likely to receive milder assessment results (p < 0.001), which is consistent with previous studies assuming that the reason for restricted subareolar abscesses in these patients is associated with squamous metaplasia of lactiferous ducts [31] .…”
Section: Discussionsupporting
confidence: 74%
“…Ciftci Ahmet Burak [21] Azizi A [22] 118 356 Not mention skin lesions [OR = 1.83,95%CI[0.12-3.00] ,P = .01] Qing Ting Tan [23] 20 93 132 inflammatory signs and symptoms* Corynebacterium infection* Pelin Basim [24] is longer compared to unilateral cases. In terms of symptoms, bilateral GLM shows similar characteristics to unilateral GLM, although the severity of symptoms was not compared in this retrospective study as the clinical data did not provide such information.…”
Section: Discussionmentioning
confidence: 99%
“…In reviewing reports on risk factors for GLM recurrence in domestic and international studies, [19][20][21][22][23][24] nipple discharge, skin damage, surgery, breast abscess, and smoking history were commonly identified as independent risk factors for unilateral recurrence (Table 4). This study found statistical differences in 4 variables: fertility, nipple development, CD4 absolute value, and CD4/CD8 ratio, through univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the biopharmaceutical industry, it is common to have multiple valuable components present in a single feedstock, such as albumin and globulin in plasma/serum. To avoid wasting any of these components, strategies have been developed to address this issue. One such strategy is to recover different components with corresponding technologies in turn.…”
Section: Introductionmentioning
confidence: 99%